Biological B-cell stimulatory biomarkers in HIV-associated non-hodgkin lymphoma - Cruywagen, Lauren Ashton (My University, 2016)
Background: Human Immunodeficiency Virus (HIV) is an epidemic in South Africa with a rise in AIDS-defining malignancies, particularly Non-Hodgkin Lymphoma (NHL). B-cell stimulatory markers have been implicated in the risk and development of HIV-associated NHL. The mechanisms of the pathogenesis of HIV-associated NHL have not been fully elucidated but include: B-cell hyperactivation mediated by the over production of cytokines as a consequence of reduced immunosurveillance associated with CD4+ T-cell deficiencies. AIM: This study aimed to investigate and quantify the expression of B-cell stimulatory biomarkers in plasma and determine their contribution to lymphomagenesis in an HIV positive South African cohort. Methods: Plasma samples from HIV positive patients with confirmed NHL and HIV positive patients without evidence of lymphoma were assessed for ten cytokines: Interleukin (IL) IL-1β, IL-2, IL-4, IL-5, IL-6, IL-8, IL-10, granulocyte-macrophage colony stimulating factor (GM-CSF), interferon gamma (IFNγ ) and tumour necrosis factor alpha (TNFα), as well as two soluble factors, sCD23 and sCD30 by Luminex Technology and ELISA respectively. Peripheral blood mononuclear cells from a HIV positive patient with Burkitts lymphoma were used to establish an in vitro culture. Results: Cytokines IL-6, IL-8 and IL-10 concentrations (pg/ml) were significantly elevated in HIV positive patients with NHL compared to the HIV positive controls. Soluble factors CD23 and CD30 concentrations (U/ml) were also elevated in HIV positive patients with NHL. Conclusion: IL-6, IL-8 and IL-10 may play a key role in stimulating B-cell proliferation and lymphomagenesis. IL-6 and IL-8 are pleiotropic pro-inflammatory cytokines, and IL-10 an anti-inflammatory and/or regulatory cytokine, that act as growth factors in a paracrine or autocrine manner for HIV-associated lymphoma cells.
Dissertation submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Master of Science in Medicine in the branch of Molecular medicine & Haematology Johannesburg, 2016
Keywords: HIV; Lymphoma, Non-Hodgkin; B-Cell Activating Factor